Engineering graphitic carbon nitride (g-C3N4) for catalytic reduction of CO2 to fuels and chemicals: strategy and mechanism. Issue 15 (16th July 2021) - Lu, Qingqing; Eid, Kamel; Li, Wenpeng; Abdullah, Aboubakr M.; Xu, Guobao; Varma, Rajender S.
Abstract : This review summarises the structural-compositional engineering of carbon nitride (g-C3 N4 ) for electrocatalytic and photocatalytic CO2 reduction to chemicals and fuels experimentally and theoretically. Abstract : The reduction of carbon dioxide to useful fuels/chemicals, such as methane, formic, and methanol, is an innovative way to address looming energy and environmental issues. Graphitic carbon nitride (g-C3 N4 ), as a greener and low-cost catalyst for the electrocatalytic and photocatalytic carbon dioxide reduction reaction (CO2 RR) to provide usable fuels, is endowed with numerous appealing attributes, e.g., Earth-abundant resources, facile synthesis, metal-free nature, catalytic properties, and unique thermal-physical–chemical stability. Articles on the use of g-C3 N4 for CO2 transformation have increased significantly in the past decade, and it is important to provide timely updates in this emerging and active research area. This review emphasizes the rational structural engineering of g-C3 N4, including doping ( i.e., metal, non-metal, and molecular) and heterojunction formation ( i.e., metal, metal oxide, metal phosphide, metal hydroxide, metal complex, Ag-halides, and carbon materials) for electrocatalytic, photoelectrocatalytic, and photocatalytic CO2 RR. Besides, an in-depth deciphering of the CO2 RR mechanism from experimental, theoretical, and fundamental concepts is provided, including deliberation on the sources/emission and strategies to avoid/reduce CO2 emission. Lastly, a brief conclusion and outlook on the challenges and future prospects are highlighted to assist further in the rational design of the g-C3 N4 -based catalyst as a selective and efficient catalyst for the CO2 RR.